Contribution of Mouse Embryonic Stem Cells and Induced Pluripotent Stem Cells to Chimeras through Injection and Coculture of Embryos - Jitong Guo; Baojiang Wu; Shuyu Li; Siqin Bao; Lixia Zhao; Shuxiang Hu; Wei Sun; Jie Su; Yanfeng Dai; Xihe Li (Stem Cells International)
Blastocyst injection and morula aggregation are commonly used to evaluate stem cell pluripotency based on chimeric contribution of the stem cells. To assess the protocols for generating chimeras from stem cells, 8-cell mouse embryos were either injected or cocultured with mouse embryonic stem cells and induced pluripotent stem cells, respectively. Although a significantly higher chimera rate resulted from blastocyst injection, the highest germline contribution resulted from injection of 8-cell embryos with embryonic stem cells. The fully agouti colored chimeras were generated from both injection and coculture of 8-cell embryos with embryonic stem cells. Additionally, microsatellite DNA screening showed that the fully agouti colored chimeras were fully embryonic stem cell derived mice. Unlike embryonic stem cells, the mouse chimeras were only generated from injection of 8-cell embryos with induced pluripotent stem cells and none of these showed germline transmission. The results indicated that injection of 8-cell embryos is the most efficient method for assessing stem cell pluripotency and generating induced pluripotent stem cell chimeras, embryonic stem cell chimeras with germline transmission, and fully mouse embryonic stem cell derived mice.